2016
DOI: 10.14202/vetworld.2016.1456-1460
|View full text |Cite
|
Sign up to set email alerts
|

Multiple infections of Anaplasma platys variants in Philippine dogs

Abstract: Aim:Anaplasma platys, the causative agent of infectious canine cyclic thrombocytopenia, is a tick-borne pathogen that also has been implicated as potentially zoonotic. To provide molecular evidence on the multiple infections of A. platys variants in Philippine dogs.Materials and Methods:DNA fragments of A. platys from infected dogs in the Philippines were molecularly characterized. For screening, 25 dogs suspected to have canine anaplasmosis were tested using a 16S rRNA-based nested polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Interestingly most genotypes differing in just one nucleotide were found in cattle, goat or blood-fed mosquitoes in China, but the Candidatus Anaplasma camelii genotype was not found in China. However, the largest diversity of similar genotypes was found in Asia (China, Philippines, Malaysia), and the same is the case with A. platys which differs only by one nucleotide [10,33,34,53,54]. The occurrence of identical genotypes in Iran, Bangladesh and Malaysia might suggest that Candidatus Anaplasma camelii did not originate in camels in the Middle East but in Eastern Asia.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly most genotypes differing in just one nucleotide were found in cattle, goat or blood-fed mosquitoes in China, but the Candidatus Anaplasma camelii genotype was not found in China. However, the largest diversity of similar genotypes was found in Asia (China, Philippines, Malaysia), and the same is the case with A. platys which differs only by one nucleotide [10,33,34,53,54]. The occurrence of identical genotypes in Iran, Bangladesh and Malaysia might suggest that Candidatus Anaplasma camelii did not originate in camels in the Middle East but in Eastern Asia.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in Algeria [2], Senegal [27] and Tunisia [28] similarly reported this pathogen in cattle. Yang et al [29] suggested a possibility of domestic ruminants acting as alternative hosts or reservoirs for A. platys which is typically a canine pathogen [30]. Therefore, the detection of this pathogen in cattle raises questions of host specificity as earlier speculated [31].…”
Section: Discussionmentioning
confidence: 99%
“…Zobba et al [9] noted that several domestic ruminants can harbor a number of strains of A. platys although these strains have different cell tropism compared to those infecting dogs. The ruminant strains infect neutrophils and are thought to be the ancestral pathogens that evolved to adopt to the canine platelets instead [9,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Swiss national center for tick-borne diseases sequentially tested the same 8'000 batch of ticks for the presence of the agent of tick-borne encephalitis [32], for chlamydiae [13] as well as Anaplasma and Coxiella (Pilloux et al, unpublished). Not only different pathogen species were found coinfecting ticks and hosts, but also coinfections with multiple strains of the same pathogen have been reported [33,34]. Detection of coinfections can be achieved following standard PCR or more demanding technologies such as microfluidic highthroughput real-time PCR.…”
Section: Why Coinfections Are Important?mentioning
confidence: 99%